Neonatal jaundice and associated factors in public hospitals of southern Ethiopia: A multi-center cross-sectional study - Agegnehu Bante; Muluken Ahmed; Nega Degefa; Shitaye Shibiru; Manaye Yihune (Heliyon, 2024)
Background: Neonatal jaundice is one of the most prevalent problems, affecting over a million newborns globally every year. It increases the likelihood of hospitalization, lifetime disability, and death, particularly in low and middle-income countries. Despite its impact and diverse risk factors, neonatal jaundice remains underappreciated in developing nations such as Ethiopia. As a result, this study aimed to determine the magnitude and associated factors of jaundice in newborns admitted to public hospitals in south Ethiopia. Methods: A facility-based cross-sectional study was conducted among 417 newborns from October 1, 2020, to April 30, 2021. The data was collected using pretested interviewer-administered questionnaire and checklist. Jaundice and its severity were assessed using the physician's diagnosis and the Kramer scale. Open data kit tools and Stata version 16.0 were used for data collection and analysis, respectively. Bivariable and multivariable analyses were used to identify factors associated with neonatal jaundice. An odds ratio with a 95 % confidence interval was used to assess the direction and strength of the association. Results: Out of the newborns, 24.46 % [95 % CI: 20.42–28.88] encountered neonatal jaundice. Being male [AOR: 1.81, 95 % CI: 1.06, 3.12], birth injuries [AOR: 3.01, 95 % CI: 1.27, 7.12], perinatal asphyxia [AOR: 2.10, 95 % CI: 1.18, 3.76], hyaline membrane disease [AOR: 2.16, 95 % CI: 1.16, 4.00], sepsis [AOR: 3.30, (95 % CI: 1.67, 6.54], the combined effect of low birth weight and prematurity [AOR: 1.88, 95 % CI: 1.06, 3.35], and maternal alcohol abuse during pregnancy [AOR: 2.46, 95 % CI: 1.02, 5.94] were significantly associated with neonatal jaundice. Conclusion: The burden of neonatal jaundice was high in the hospitals studied. Early detection and treatment of neonatal problems, counseling pregnant women to avoid consuming any level of alcohol, strict monitoring of labor and delivery, improving antenatal care utilization, and pre-discharge universal bilirubin screening of newborns are essential to reduce the incidence and complications of jaundice. The findings of this study will be used as input to initiate interventions and conduct further studies.